Leveraging Heterogeneity in Systemic Lupus Erythematosus for New Therapies. Issue 2 (February 2021) - Allen, Marilyn E.; Rus, Violeta; Szeto, Gregory L.
Abstract : Systemic lupus erythematosus (SLE) is a multisystem, chronic autoimmune disease where treatment varies by patient and disease activity. Strong preclinical results and clinical correlates have motivated development of many drugs, but many of these have failed to achieve efficacy in clinical trials. FDA approval of belimumab in 2011 was the first successful SLE drug in nearly six decades. In this article, we review insights into the molecular and clinical heterogeneity of SLE from transcriptomics studies and detail their potential impact on drug development and clinical practices. We critically examine the pipeline of SLE drugs, including past failures and their associated lessons and current promising approaches. Finally, we identify opportunities for integrating these findings and drug development with new multidisciplinary advances to enhance future SLE treatment. Highlights: Advances in transcriptomic analyses have revealed systemic lupus erythematosus (SLE) patient classifications and underscored the importance of type I interferon-dependent and -independent gene signatures in disease pathogenesis. Results from these studies offer new insights into treatment design to target different immune cell types, proteins, and signaling pathways. Biologic drug development broke a five-decade gap with belimumab, the first U.S. FDA approved drug for adults and children with moderate-to-severe SLE. The FDA also granted fast-track designation to telitacicept for SLE and obinutuzumab for proliferative lupus nephritis. In 2020, ClinicalTrials.gov shows >400 trials registered for SLE and >100 for lupus nephritis. Refinement of clinical trial design may improve the success of therapies in development.